2005
DOI: 10.1159/000089090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Viral Hepatitis on Graft Survival in Saudi Renal Transplant Patients

Abstract: Background: In Saudi Arabia the prevalence of hepatitis C among hemodialysis patients is very high ranging from 60 to 80%. A large number of these dialysis patients go for renal transplant, resulting into a higher prevalence of hepatitis C virus (HCV) infection in renal transplant patients. Yet no current systematic report is available on the influence of hepatitis C status on patient and graft survival. The present study was therefore undertaken to address this objective. Methods: Retrospective analysis of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…The prevalence of HCV infection of 16.1% found in these patients in GO is almost 12 times greater than that observed among local blood donors (1.4%) (Martins et al 1994). Nevertheless, relative to other Brazilian renal transplant recipient populations, this prevalence is lower than those reported in the cities of Porto Alegre (33%) (Corrêa et al 2003) and Campinas (54%) (Giordano et al 2003); it was, however, in accordance with those carried out in other countries, where rates have been found to range from 7.2% to 63.8% (Fehr et al 2003, Mitwalli et al 2006). In addition, the prevalence among RTP we determined is similar to that reported for hemodialysis patients in GO (16.4%) ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The prevalence of HCV infection of 16.1% found in these patients in GO is almost 12 times greater than that observed among local blood donors (1.4%) (Martins et al 1994). Nevertheless, relative to other Brazilian renal transplant recipient populations, this prevalence is lower than those reported in the cities of Porto Alegre (33%) (Corrêa et al 2003) and Campinas (54%) (Giordano et al 2003); it was, however, in accordance with those carried out in other countries, where rates have been found to range from 7.2% to 63.8% (Fehr et al 2003, Mitwalli et al 2006). In addition, the prevalence among RTP we determined is similar to that reported for hemodialysis patients in GO (16.4%) ).…”
Section: Discussionsupporting
confidence: 78%
“…These genotypes have distinct geographical distributions. Furthermore, the genotyping of HCV isolates is a useful tool for establishing the source of outbreaks in hemodialysis centers and other nosocomial settings (Zein 2000, Simmonds et al 2005 The prevalence of HCV infection has been reported to range from 7.2% among renal transplant recipients (RTP) in Switzerland to 63.8% in Saudi Arabia (Mitwalli et al 2006, Fehr et al 2003. In Brazil, a continental country, epidemiological data concerning HCV infection in renal transplant patients are still rare (Corrêa et al 2003, Giordano et al 2003, and little is known about the genetic diversity of HCV isolates in these patients (Giordano et al 2003, Perez et al 2003.…”
mentioning
confidence: 99%
“…In a previous survey in Iran, HCV RNA was detected in 6.4% of liver transplant recipients (26). Moreover, the infection in renal transplant recipients varies between 2.6% and 66% in different geographical areas of the world (27)(28)(29).…”
Section: Discussionmentioning
confidence: 96%
“…However, HCV-infected renal allograft recipients with abnormal liver function had inferior survival rates. Several other studies [131,132,133,134,135], with the exception of one [136], with shorter than 10-year follow-up periods reported no adverse impact of HCV infection on graft and/or patient survival. The promising results of the aforementioned studies suggest that for many patients, the benefits of renal transplantation outweigh its potential risks imposed by immunosuppression.…”
Section: Natural History and Liver Histopathology In Hcv-infected Hd mentioning
confidence: 99%